2013
DOI: 10.1089/apc.2013.0096
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Screening Guidelines for Hepatitis C Among HIV-Positive Patients

Abstract: T here is increasing awareness of an on-going epidemic of sexually-transmitted acute hepatitis C virus (HCV) infection among HIV-infected men who have sex with men (MSM). The percentage of all HIV infected people who also have HCV ranges from 15% to 30%, and one study reported that 37% of people with HIV were co-infected with HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…1 However, even when HIV providers are aware of guidelines calling for vaccination and screening for co-morbid conditions, compliance with these guidelines may be low. 21 HIV providers and researchers should investigate ways to improve the outpatient quality of care. The Patient Centered Medical Home, a team-based model of care that emphasizes personalized, accessible, high-quality, and comprehensive care over time and across healthcare settings, 22 has been shown to improve the delivery of preventative care services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, even when HIV providers are aware of guidelines calling for vaccination and screening for co-morbid conditions, compliance with these guidelines may be low. 21 HIV providers and researchers should investigate ways to improve the outpatient quality of care. The Patient Centered Medical Home, a team-based model of care that emphasizes personalized, accessible, high-quality, and comprehensive care over time and across healthcare settings, 22 has been shown to improve the delivery of preventative care services.…”
Section: Discussionmentioning
confidence: 99%
“…We found that older age groups (ages 40-49 and ‡ 50) met more performance measures than the youngest age group (ages [18][19][20][21][22][23][24][25][26][27][28][29]. Providers may be more cognizant of the need for certain tests in adults ‡ 40 years of age (i.e., lipid screening).…”
Section: Discussionmentioning
confidence: 99%
“…11 Despite this, evidence suggests that people living with HIV are not routinely screened for HCV infection. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Fourth, these findings may underrepresent the magnitude of the issue, as adherence to screening guidelines is imperfect, and more patients may be affected. 10 Finally, BCTT involves the use of pegylated interferon and ribavirin, and these medications can have their own drug-drug interactions, and this could upwardly drive up the number of CSDDI. This was not the case in this study.…”
mentioning
confidence: 99%